A flexibility study on the role of ChatGPT in language learning - Leung, Chi Hong (Asian Journal of Contemporary Education, 2025)
This study aims to investigate the efficacy of ChatGPT, a widely-used chatbot, in supporting language learning. It seeks to explore how AI-driven language education tools, particularly ChatGPT, can enhance language learning goals through personalized experiences and prompt feedback. The research evaluates ChatGPT's role in language education by assessing its capacity to deliver tailored learning paths, recommend personalized content, provide instant feedback, and empower learners to take control of their educational journey. It investigates how ChatGPT reinforces language learning through illustrative dialogues and interactive grammar explanations. The findings indicate that ChatGPT offers personalized learning experiences by analyzing learners' preferences, styles, and emotional states. It furnishes tailored content, immediate feedback, and fosters independent learning. ChatGPT proves effective in supporting language learning objectives, facilitating efficient acquisition of new knowledge and skills. In conclusion, ChatGPT emerges as a valuable asset for language learning, furnishing customized pathways, instant feedback, and resources tailored to learners' requirements. It empowers students to actively engage in their learning process, providing support in grammar comprehension and exercise preparation. While acknowledging the benefits, it is crucial to consider both advantages and drawbacks when utilizing ChatGPT for language learning. This study underscores the practical implications of integrating ChatGPT and other AI-driven language learning tools in educational contexts. It proposes strategies for leveraging ChatGPT effectively, such as utilizing its personalized features, prompt feedback mechanisms, and content recommendations. Additionally, it addresses strategies to mitigate potential challenges and enhance the overall language learning experience through ChatGPT.